Factors Affecting the Phenomenon of Poverty in Iraq (Anbar as a Model) - Mikhli, Ayad Mohammed; Salem, Nadia Talib (Journal of Cultural Analysis and Social Change, 2025)
Poverty is a complex issue that results from the interaction of social, political, and economic elements that affect people's capacity to achieve their most basic need. Developing effective measures to lessen its effects on people and society is made possible by an understanding of these elements. With an emphasis on examining the social and economic circumstances faced by low-income families and determining the consequences of the increase in the poverty line in the study region, the study aims to investigate the variables contributing to the phenomenon of poverty in Anbar. A descriptive approach was used to interpret and analyze the findings of the study on the factors influencing the poverty phenomenon in Anbar. Additionally, the results of the questionnaire for the year 2024 were analyzed to determine the percentages of data pertaining to the phenomenon of poverty, which came to 452 families in the governorate. The spread of poverty in Anbar province dates back to a long history of economic and political factors. Due to the absence of employment prospects that coincide with population growth, this situation has gotten worse in recent years. High unemployment rates have resulted from this, making it difficult for many families to meet their basic necessities. This has had a detrimental effect on many facets of provincial life and aided in the rise of significant social issues and phenomena, including drug misuse, domestic violence, begging, and crime. One of the significant topics this study addresses is the poverty phenomena in Anbar. It concentrated on examining the political, social, economic, and demographic elements that fueled the development of poverty, including rising family sizes, fast population growth, inadequate education, joblessness, low incomes, and the worsening security conditions brought on by crises. The study's objectives are to present a scientific examination of these variables and offer suggestions for lowering poverty. Keywords: economic and social causes, poverty, and Anbar